2019
DOI: 10.3390/app9040686
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation into the Structural and Functional Performance of Graphene Nano-Platelet (GNP)-Doped Asphalt

Abstract: With the increase in the demand for bitumen, it has become essential for pavement engineers to ensure that construction of sustainable pavements occurs. For a complete analysis of the pavement, both its structural and functional performances are considered. In this study, a novel material (i.e., Graphene Nano-Platelets (GNPs)) has been used to enhance both of the types of pavements’ performances. Two percentages of GNPs (i.e., 2% and 4% by the weight of the binder) were used for the modification of asphalt bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A new material Graphene Nano-Platelets (GNPs), has been used to enhance pavements' structural and functional performances [4]. The results showed that GNPs improved not only the rutting resistance of the pavement but also its durability.…”
Section: Binders' Modificationmentioning
confidence: 99%
“…A new material Graphene Nano-Platelets (GNPs), has been used to enhance pavements' structural and functional performances [4]. The results showed that GNPs improved not only the rutting resistance of the pavement but also its durability.…”
Section: Binders' Modificationmentioning
confidence: 99%
“…Recently, carbon and graphene family nanomaterials have been used for asphalt modification [47], such as graphene nanoplatelets (GNPs). The addition of GNP in the mixture leads to an improvement in flexural strength at low temperatures, better performance at high temperatures [48] and easier compaction [49]. However, only a few studies focused on the microwave heating and healing efficiency of asphalt mixture containing graphene nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The cohesive and adhesive bonding interactions of asphalt-aggregate systems are strongly influenced by the Lifshitz-van der Waals interactions, and the acid-base interaction components [14]. Some examples of self-healing asphalt pavement technologies commonly mentioned in the literature review that possess the potential to reverse the fracture failure process and restore the loss in the mechanical performance properties (e.g., stiffness and strength) and functionality suffered by the asphalt pavements during their service life include (but are not limited to these solutions): (1) Encapsulated chemical products containing rejuvenator oil agents to repair broken bonds due to the accumulated micro-crack damage caused by the fatigue cracking process [15][16][17]; (2) magnetic induction heating technique in combination with conductive materials (e.g., steel wool, steel fibers, metal particles, carbon black, and graphite) to speed up the asphalt healing process [18][19][20][21][22][23]; (3) infrared heating technique [24][25][26]; (4) microwave radiation heating energy in combination with ferrous particle aggregates (EAF slag) in order to accelerate the heating and healing capability of the asphalt mixtures [27][28][29][30]; (5) the addition of Nanomaterials into the asphalt mixture design, such as carbon nanotubes (CNTs), carbon black nanoparticles (CBNPs), and graphene nanoplatelets (GNPs); the GNPs nanoparticles especially improve the resistance to permanent deformation, moisture damage, skid resistance [31], flexural strength at low temperatures, and increase the cohesion recovery ratios of the mixtures [32]; and (6) industrial microwave heating applications through a mobile microwave power unit for pavement maintenance works [33,34], with emphasis being placed on recycling techniques for surface layers [35].…”
Section: Introductionmentioning
confidence: 99%